Assessing and managing sustainability in international perspective: Corporate sustainability across cultures - towards a strategic framework implementation approach - Martin Gerner (International Journal of Corporate Social Responsibility (JCSR), 2019)
Introduction: Sustainability constitutes an essential element in corporate contexts by now. Corporate sustainability may be addressed differently, either selectively or integrated. The holistic approach opted for primarily focuses on conveying aspects of corporate sustainability across different socio-cultural contexts. In doing so, the full quadruple scope of sustainability dimensions is considered cornerstone of a well-chosen case-study design. Such particular reference prototypically exemplifies business models in highly volatile commodity markets. Continuously longing for optimization and rationalization due to creativity and productivity gains, the company is predominantly challenged by changing customer needs resulting from digitization as mega trend of the twenty-first century. Case description: Alluding to the business of stationery and professional office supplies, this case study aims at advocating the systematic proceeding of how to strengthen corporate sustainability through both embracing existing and evolving culture-bound approaches of sustainability vis-à-vis a framework implementation strategy and related guidelines for implementation at operational level. The essential quest is how to convey aspects of corporate sustainability across different socio-cultural contexts? Aiming at contributing to some kind of framework implementation strategy this implies reflecting upon assessing the status quo of corporate sustainability-related strategic approaches, activities and initiatives, means and instruments (sustainability performance); identifying universal and culture-bound drivers (sustainability opportunity); and deducing operational guidelines towards stakeholder awareness, selected strategic options, projects and best practices (sustainability commitment). Given the theoretical background of corporate sustainability and related contexts, impetus for operationalizing is created by triple means of: * Adopting an extended and generic life-cycle assessment (LCA) as core analytic framework and structuring element, corresponding with the value-chain-oriented approach of business segments, * Applying the multi-method paradigm of methodological triangulation, including stakeholder observation, expert interviews and company resources, and * Framing major characteristics as case study according to principles of qualitative content analysis. Discussion and evaluation: Assuming that corporate sustainability may be conducive to foster innovation and evolution of products and services, the company's sustainability performance, sustainability opportunity and sustainability commitment is systematically analysed in line with the generic life cycle. By covering supply chain, production, distribution/packaging, service/use, and end-of-life, the status quo of corporate sustainability-related strategic approaches is assessed first, followed by identifying universal and culture-bound drivers to corporate sustainability, and concluding operational guidelines in terms of stakeholder awareness, selected strategic options, projects and best practices. A resultant framework implementation strategy provides four strategic options of product stewardship, operational efficiency, innovative transformation, and adaptive responsiveness, and attributing them to cross-sectoral aspects of innovation, business-model evolution and socio-cultural contexts, first and foremost. Innovative value is added by systematically and holistically assessing corporate sustainability driven by grounded heuristics, multi-dimensional and culture-inclusive rationale, and implementation-focused impetus. Conclusions: It can be concluded that adequately taking socio-cultural contexts into consideration may constitute a strategic and influential driving force to corporate sustainability, that strengthening cultural aspects of corporate sustainability may push the innovative capacity for business-model evolution; and that highlighting comparative advantages of sustainability-oriented manufacturing and branding favours the identification of business cases for sustainability. In a nutshell, corporate commitment to/for sustainability is essentially advised in challenging times of economic turbulence and rapid changes; it represents the window of opportunity to revisit assumptions and value propositions of long-lived business models.
Keywords: 650; Sustainability; Corporate sustainability; Corporate responsibility; CR; CSR; Sustainability assessment; Life-cycle assessment; LCA Strategic; Performance; Opportunity; Commitment; Universal; Cultural; Framework implementation strategy